ISOLATION AND STRUCTURAL CHARACTERIZATION OF SECONDARY METABOLITES FROM Actinophytocola sp. K4-08 RARE ACTINOMYCETE WITH POTENTIAL BIOSYNTHETIC CAPABILITY - Nur Huda Mohd Zin; Zainal Abidin, Zaima Azira; Abdul Malek, Nurfathiah; Azizan, Nur Hafizah; Darnis, Deny Susanti (International Journal of Allied Health Sciences, 2019)
Thousands of antibiotics have been found from different actinomycetes, but there was less study recorded on isolation, characterisation and antimicrobial properties of rare actinomycete, especially Actinophytocola sp. K4-08, making it a prominent source of novel bioactive compounds. Therefore, the present study was carried out to isolate, characterise and identify the antimicrobial activity of rare actinomycete, Actinophytocola sp. K4-08. Actinophytocola sp. K4-08 was successfully isolated from Kuantan mangrove sediment and growth on starch-yeast extract agar (SYE) medium. Abundant cream coloured substrate mycelium was formed on SYE, and no obvious diffusible pigment was produced within 21 days of incubation. Partial 16S rRNA gene sequence revealed that Actinophytocola sp. K4-08 possessed 99% similarity to Actinophytocola sediminis YIM 75636.Moreover, both PKS-I and NRPS genes, both of which usually related to secondary metabolite potential were detected in this isolate through PCR amplification. Preliminary screening using cross streak test showed that Actinophytocola sp. K4-08 displayed antibacterial activity against B. subtilis and S. aureus. Its crude ethyl acetate extracts also displayed inhibitory activity against B. subtilis, further confirming the antimicrobial properties of this isolate. Actinophytocola sp. K4-08 was cultured in SYE broth followed by centrifugation to separate the cells and the supernatant. Crude ethyl acetate (EA) extract from the supernatant was also prepared, and cells of Actinophytocola sp. was extracted with methanol (ME) extract. All extracts (supernatant and cells) produced dark orange solid and yellow coloured crude. Disc diffusion assay against B. subtilis with a concentration of 20, 40, 60, 80 and 100 Âµg/disc was conducted to check on the antibacterial capabilities of the extracts. All extracts displayed weak inhibition activity against B. subtilis. Although the extracts produced weak antibacterial activity, nevertheless, the potential of Actinophytocola sp. indicated potential as a bioactive compound producer that is worth exploring. Purification of crudes using TLC shows a few purified compounds can be separated from EA and ME crude each using highly polar mobile phase. FTIR spectrum of EA and ME crude shows the presence of alcohol, alkyl, esters and aromatic functional groups. Further investigation is needed in an attempt to purify further and elucidate potential bioactive compounds produced by Actinophytocola sp. K4-08 using HPLC, LCMS and NMR.